Efektivitas Penerapan Trainer sebagai Media Pembelajaran Dasar Listrik Elektronika - Ismul Uyun; Dwiprima Elvanny Myori (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to determine the application effectiveness of learning trainers in Basic Electrical and Electronics class at SMK Negeri 1 Lembah Melintang. The low learning outcomes of students and the struggle in answering practical questions during exams are caused by their lack of enthusiasm and self-containment during the learning process, so it is necessary to implement the trainers optimally. The method in this study was pre-experimental, using a one-group pretest-posttest research design. The research subjects were 32 students of class X TITL2. The data collection mechanisms utilized pretest and posttest evaluation. The normalized gain was used as data analysis to examine the effectiveness of the learning trainers. The results showed that the application of this media trainer was concluded ineffective. This conclusion can be seen from the moderate normalized gain of 0.32 or equivalent to 32% and categorized as ineffective.